BELE KAMPUNG SEKODI: INTERAKSIONISME SIMBOLIK - Mita Rosaliza; Tengku Syarifah Dzikra Hanania; Tengku Abyan Hanif (Jurnal Ilmu Budaya, 2024)
The environment is one of the most important aspects of a community. So is the Sekodi community with the Bele Kampung tradition. This research is intended to obtain an overview of (a) To find out the process of implementing the Bele Kampung tradition in the Tanjung Community of Sekodi Village. (b) To find out the meaning of the Bele Kampung tradition in the people of Tanjung , Sekodi Village. This research uses a descriptive method with a qualitative research type used to reveal and describe how the Bele Kampung tradition occurs in maintaining the village in Sekodi village, Bengkalis Regency. Data were obtained from informants/speakers through interviews, recording and observation. The data obtained was then analyzed. Based on the research results. The symbols in the Bele Kampung tradition contain complex and deep meanings. The Bele Kampung tradition is carried out at the house of the implementing shaman once a year after a deliberative decision. It is done for three consecutive days. On the first day, they send a pebuang tool to the Tanjung and recite a congratulatory prayer there, then return home with water for bathing on the third day. On the second day, there is swinging, and the community is given words of advice and patted with fresh flour before swinging. After swinging and patting fresh flour, they then send pebuang tools to Tumu, Nipah, and Baran, and throw away the ancak used for bathing. On the third day, residents of Tanjung from three sacred places: Tanjung, Nipah, and Tumu. This tradition is very useful in maintaining the cleanliness and preservation of the village traditionally and the clean culture continues to be well maintained